Note to the Spanish pharmacopoeia, IX edition: Bismuth subnitrate - García Villanova, R.; Thomas, J.; Bosch, F. (Ars Pharmaceutica (Internet), 1964)
A gravimetric and complexometric technics of evaluation of bismuth subnitrate has been revised. We recommended a complexometric technic, using EDTA and a potassium iodide, Pyrocatechol Violet and thiourea as indicators indifferently, in order to include it in the new Spanish Pharmacopeia edition.